2019
DOI: 10.1101/700070
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In-depth and 3-Dimensional Exploration of the Budding Yeast Phosphoproteome

Abstract: Phosphorylation is one of the most dynamic and widespread post-translational modifications regulating virtually every aspect of eukaryotic cell biology. Here we present a comprehensive phosphoproteomic dataset for budding yeast, comprised of over 30,000 high confidence phosphorylation sites identified by mass spectrometry. This single dataset nearly doubles the size of the known phosphoproteome in budding yeast and defines a set of cell cycle-regulated phosphorylation events. With the goal of enhancing the ide… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 59 publications
1
48
0
Order By: Relevance
“…Looking ahead, it will be crucial to develop more efficient approaches for identifying functional phosphorylation events within the large phosphoproteomic datasets. One possibility is to use structural prediction analysis to identify phosphorylation events that are likely to impair protein function (such as disrupting protein-protein or protein-DNA interactions) (preprint: Lanz et al, 2019). In conclusion, a holistic understanding of the role and action of DNA damage signaling kinases will require powerful technologies capable of quantitatively monitoring the full extent of the phosphoproteome in combination with systematic approaches for functional and mechanistic analyses.…”
Section: What's Next? Toward a Holistic View Of The Dna Damage Signalmentioning
confidence: 99%
“…Looking ahead, it will be crucial to develop more efficient approaches for identifying functional phosphorylation events within the large phosphoproteomic datasets. One possibility is to use structural prediction analysis to identify phosphorylation events that are likely to impair protein function (such as disrupting protein-protein or protein-DNA interactions) (preprint: Lanz et al, 2019). In conclusion, a holistic understanding of the role and action of DNA damage signaling kinases will require powerful technologies capable of quantitatively monitoring the full extent of the phosphoproteome in combination with systematic approaches for functional and mechanistic analyses.…”
Section: What's Next? Toward a Holistic View Of The Dna Damage Signalmentioning
confidence: 99%
“…Earlier high-throughput work has shown that Rgd3 contains an SH3-domain binding motif at its C-terminus capable of being recognized by the SH3-domain containing factors Bbc1, Lsb1, Lsb3, and Ysc84, all of which participate in actin organization in endocytosis ( Figure 7D) (Tonikian et al, 2009). Moreover, the serine and threonines flanking the proline residues of this motif have been found to be phosphorylated in a recent yeast whole phospho-proteome analysis (Lanz et al, 2019). We therefore explored the phenotype of cells in which the serine and threonine residues in Rgd3 were mutated to either alanines (AA/AA mutant) to preclude phosphorylation or aspartic and glutamic acids (DE/EE mutant) to mimic phosphorylation.…”
Section: Rgd3 Is Not Stably Associated With Endocytic Vesiclesmentioning
confidence: 84%
“…5B and C). In this sense, previous phosphomapping analyses of Yen1 revealed that there are at least 20 S/T residues at non-CDK consensus sites phosphorylated in vivo (67,68,93). Since the Yen1 ON preps we employed were not in vitrodephosphorylated, we wanted to assess if phosphorylation at those non-CDK consensus sites could also be contributing to the regulation of Yen1 activity.…”
Section: Yen1 On Displays the Same Cleavage Specificity As Yen1mentioning
confidence: 99%